Mechanism of transformation of agricultural enterprises in terms of innovative development - Diana Shelenko; Ivan Balaniuk; Liudmyla Sas; Petrо Matkovskyi; Iryna Kozak-Balaniuk (Vasyl Stefanyk Precarpathian National University, 2020)
The mechanism under study should be aimed at introducing innovative approaches to the modernization of technical l and technological cycles of production and economic processes, strengthening the competitive position of enterprises in the agrarian market and overcoming internal and external institutional barriers to enterprise development by suppressing irrational institutional influences on the functioning. The purpose of this study is to substantiate theoretical and methodological foundations and to develop applied approaches for implementing the mechanism of transformation of agricultural enterprises in a competitive environment. The scientific novelty of the obtained results lies in the substantiation of the mechanism of transformation of agricultural enterprises, which includes such components as: information and analytical tools (monitoring of the economic environment, verification and systematization of information data, establishment of essential laws and relationships, the formation of information bases of decision  making, management, design-testing apparatus (designing a perspective plan for the transformation of agricultural enterprises, pilot testing of the target project of the proposed changes in the organizational and legal form of management, adjustment of the project of transformation of enterprises) and implementation-block (formation of innovative structures of agricultural enterprises, ensuring the sequence and consistency of implementation of target changes, minimization of conflict environment in the process of transformation in balancing the duties, process responsibilities and responsibilities in terms of the structural components of the new organizational and legal system). The social and economic effect of this mechanism is achieved through a synergistic effect obtained through the functional interaction of enterprises that are able, however, to work autonomously. The practical significance of the mechanism is manifested in the ability to generate comprehensive management support in the process of transformation of agricultural enterprises, taking into account the specifics of a particular organizational and legal form of management in a competitive environment of their operation.